DEVELOPING WEB BASED DECISION SUPPORT SYSTEM FOR EVALUATION OCCUPATIONAL RISKS AT SHIPYARDS - Cebi, Selcuk; Akyuz, Emre; Sahin, Yasin (BRODARSKI INST, 2017)
In this study, a web based decision support system (WBDSS) has been developed to provide decision aid for risk analysis on occupational health and safety at shipyards. The system has been constructed as a modular structure to make its application easy for all kind of firms. The WBDSS is rule based and its database includes safety measures and risks for each tool and machine used in shipbuilding process. In addition, probability and hazard values have been involved in the case of violated measures. The frequencies of the violations that occurred in the work environment are entered to the system by the user. Hence, the system provides a decision support about the risks related to facilities and the cautions to be taken in the workplace. The developed WBDSS has the capability of determining accident, almost accident, and threat formation factors at workplace according to the changing parameters. In this aspect, it enables one to constantly monitor, check and evaluate risk preventive measures. Then, the capabilities of the suggested decision support system have been tested with different scenarios for shipyard processes. When the developed WBDSS is applied to all workplaces, it is aimed at providing a decrease in the number of accidents which cause death, occupational illness, injury, and temporary incapability.
Keywords: Web based decision support system; Risk Management; Occupational safety and health; Accident prevention; SHIPBUILDING INDUSTRY; ACCIDENTS; TURKEY; MODEL; OIL; Engineering